Historical sketch of the difference in the development of the marine sciences between Japan and the occidental countries - Terada, Kazuhiko (Universidad de Costa Rica, 1978)
At the time of the Meiji Restoration in 1868, Japan was completely underdeveloped in various aspects, prompting the government to become aware of the importance of education for the common people. One of the most important factors toward universal education was the invention of the Hiragana and Katagana alphabets, each consisting of about 50 characters, which greatly simplified and reduced the complicated Chinese symbols. This change from a cumbersome writing system to a more manageable one, made educatian possible to all levels of Japanese society. The Challenger Expedition (1872-1876) is said to have been the dawn of oceanography. Although the main orientation was research in marine biology, varios institutes in the world were founded by the beginning of the 20th century, all springing from this research in marine biology.